Development of the Chinese, Malay and Tamil translations of the Positive Mental Health Instrument: Cross-cultural adaptation, validity and internal consistency. (February 2021) - Vaingankar, Janhavi Ajit; Abdin, Edimansyah; Chong, Siow Ann; Sambasivam, Rajeswari; Shafie, Saleha; Ong, Hui Lin; Jeyagurunathan, Anitha; Wen Lau, Ying; Samari, Ellaisha; Chua, Yi Chian; Pang, Shirlene; Subramaniam, Mythily
This study describes the development and validation of Chinese, Malay and Tamil translations of the Positive Mental Health Instrument (PMHI) in a general population sample in Singapore. Translations were performed using two independent forward translations followed by expert panel discussions and tested for content, construct and language appropriateness using focus group discussions. The final translated tools were field-tested among 220 residents per language using self-administered questionnaires comprising the translated PMHI and other validity measures. Missing data, floor and ceiling effects, confirmatory factor analysis (CFA), internal consistency, item response theory differential item functioning (IRT-DIF) and criterion validity were assessed. A total of 10 PMHI-Chinese items, 26 PMHI-Malay items and six response categories and six PMHI-Tamil items were modified based on expert panel and focus group discussions. PMHI had low missing data and showed negative but acceptable skewness (<2) and kurtosis (<7) for all translations, except for the PMHI-Malay "spirituality" subscale (skewness: -2.8; kurtosis: 12.5). CFA showed that all three PMHI translations fulfilled the original six-factor-higher-order structure (RMSEA = 0.05, CFI = 0.962, TLI = 0.96). Cronbach's alpha coefficients for total PMHI were 0.958, 0.954, 0.945 and 0.949 in the overall sample and the Chinese, Malay and Tamil translations, respectively. The three translations of the PMHI showed expected and significant positive ( r  = 0.116 to 0.663) and negative correlations ( r  = −0.137 to −0.574) with established measures. The findings show that the Chinese, Malay and Tamil translations of the PMHI have high internal consistency and validity in this multi-ethnic population.